2022
DOI: 10.3390/antiox11061043
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Antioxidant and Anti-Inflammatory Mechanisms Induced by Intermittent Hypobaric Hypoxia

Abstract: More than 80 million people live and work (in a chronic or intermittent form) above 2500 masl, and 35 million live in the Andean Mountains. Furthermore, in Chile, it is estimated that 100,000 people work in high-altitude shifts, where stays in the lowlands are interspersed with working visits in the highlands. Acute exposure to high altitude has been shown to induce oxidative stress in healthy human lowlanders due to increased free radical formation and decreased antioxidant capacity. However, intermittent hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Also, disruption in redox homeostasis is a cofactor in HH-induced cardiac dysfunction ( 7 ), and our findings consolidated this fact, as HIF-1α, HIF-2α and Nrf2 expression were declining in HH mice hearts. Even so, it was observed that by employing OP intervention, HIF-2α and Nrf2 but not HIF-1α expressions were rescued and sustained in OPHH mice hearts.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Also, disruption in redox homeostasis is a cofactor in HH-induced cardiac dysfunction ( 7 ), and our findings consolidated this fact, as HIF-1α, HIF-2α and Nrf2 expression were declining in HH mice hearts. Even so, it was observed that by employing OP intervention, HIF-2α and Nrf2 but not HIF-1α expressions were rescued and sustained in OPHH mice hearts.…”
Section: Discussionsupporting
confidence: 82%
“…Redox homeostasis (balance between ROS and antioxidants) signaling are major alterations occurring during chronic hypoxia ( 7 ). Hence, to elucidate the underlying mechanisms employed by the OP intervention during HH, we investigated its impact on oxidative stress regulators – hypoxia-inducible factors (HIF-1α and HIF-2α) and antioxidant response element-dependent genes regulator, nuclear factor erythroid 2–related factor 2 (Nrf2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mild hypoxic preconditioning has become a novel therapeutic target in the treatment of hypertension [ 108 ], myocardial infarction [ 109 ], cerebral ischemia [ 110 ], and depression [ 111 ]. It is even proposed as a potential application for patients with COVID-19 [ 112 ].…”
Section: Cellular Mechanisms To Cope With the Energy Crisismentioning
confidence: 99%